The reality of management - Stewart, Rosemary (London ; Sydney : Pan Books, 1986)
This book is addressed to all managers who wish to learn more about their jobs for the practical reason of becoming better managers, and to all students who seek to learn something of the realities of management. The aim of this book is to review what has been written about management in practice; to describe some of the result of social research in management which may be of value to the practicing manager and to do so, briefly, clearly and with a minimum use of jargon.
Includes index.
Includes bibliographical references: p. 205-207.
hza 30/07/2018
Loans
Keywords: Management; Industrial management